Effectiveness of the Milwaukee Protocol in Human Rabies: A Review - Kostro, Julia Maria; Novik, Lizaveta; Libera, Anna; Kozicki, Maciej; Makulec, Gabriela; Domosud, Karolina; Zienkiewicz, Damian; Papież, Magdalena; Jędra, Zofia; Bartkiewicz, Karolina (Quality in Sport, 2026)
Introduction Human rabies remains almost invariably fatal once clinical symptoms appear, despite widespread use of pre- and post-exposure prophylaxis. The so-called “Milwaukee Protocol” — a structured regimen of therapeutic coma, NMDA antagonists, antivirals and supportive care — generated intense interest after a single widely publicized survivor in 2004. Aim of the study This review summarizes current evidence on treatment of symptomatic human rabies with emphasis on the Milwaukee Protocol. Materials and Methods We synthesized published case reports, experimental studies, and review articles addressing therapies of clinical rabies and the Milwaukee Protocol. Key outcomes were survival, functional recovery, and reported adverse events. Limitations of the evidence base are highlighted. Results Documented recoveries prior to 2004 were rare but reported under intensive supportive care. The original Milwaukee Protocol case displayed substantial recovery and prompted iterative protocol versions. Subsequent application of the protocol worldwide has produced numerous reported failures; published, verifiable survivor accounts after 2004 remain scarce. Experimental data provide limited mechanistic support for core elements of the protocol. Mortality has not been convincingly reduced beyond outcomes achievable with modern intensive supportive care alone. Conclusions Current evidence does not conclusively support the Milwaukee Protocol as an effective, reproducible curative treatment for clinical rabies. High-quality clinical reporting and standardized case registries are needed before the protocol can be eventually recommended or totally abandoned. Meanwhile, prevention through vaccination of dogs and timely post-explosure prophylaxis remains the cornerstone of rabies control.